1975
DOI: 10.1002/bjs.1800621014
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormones in breast disease

Abstract: Serum concentrations of oestradiol 17beta and progesterone were measured daily throughout one menstrual cycle in 32 normal women, 32 women with benign disease of the breast and 10 women with cancer of the breast. In normal women concentrations varied with age. Women with cysts had concentrations of oestradiol 17beta which were significantly higher than normal. In women with cancer the concentrations of oestradiol 17beta and progesterone were significantly higher than normal, but the difference was very small a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

1983
1983
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 13 publications
(10 reference statements)
1
9
0
1
Order By: Relevance
“…In contrast to the claims that progesterone is low during the luteal phase, England et al [50] reported elevated luteal progesterone in a small group of women with cystic disease aged 40-50 years. The third possibility that progesterone levels are normal, has been reported by Swain et al [186], England et al [50], Geller et al [67], and Walsh et al [198].…”
Section: (A) Estrogens and Progesteronementioning
confidence: 79%
See 1 more Smart Citation
“…In contrast to the claims that progesterone is low during the luteal phase, England et al [50] reported elevated luteal progesterone in a small group of women with cystic disease aged 40-50 years. The third possibility that progesterone levels are normal, has been reported by Swain et al [186], England et al [50], Geller et al [67], and Walsh et al [198].…”
Section: (A) Estrogens and Progesteronementioning
confidence: 79%
“…The third possibility that progesterone levels are normal, has been reported by Swain et al [186], England et al [50], Geller et al [67], and Walsh et al [198].…”
Section: (A) Estrogens and Progesteronementioning
confidence: 88%
“…Pollow et al (1977) found maximum activity in normal breast tissue at mid cycle and during the early secretory phase. While progesterone may effect an increase in I7pHSD activity in premenopausal women, it is unlikely that the same will be true for postmenopausal women since circulating progesterone concentrations are very low (England et al, 1975). At present however, no data are available for progesterone concentrations in breast tumours or normal breast tissue.…”
Section: Discussionmentioning
confidence: 93%
“…Several hormonal imbalances with potential causative roles in cyclic mastalgia have been investigated, with contradictory results [5]. Potential candidates include absolute or relative hyperestrogenism [6], luteal insufficiency [7], hyper-prolactinemia [8], and hyperandrogenism [9]. However, premenstrual mastalgia is unequivocally worsened by exogenous estrogens and improved by suppression or elimination of the ovarian cycle [4].…”
Section: Introductionmentioning
confidence: 99%